A High‐Throughput Platform for Formulating and Screening Multifunctional Nanoparticles Capable of Simultaneous Delivery of Genes and Transcription Factors. Issue 1 (17th November 2015) - Liu, Yang; Du, Juanjuan; Choi, Jin‐sil; Chen, Kuan‐Ju; Hou, Shuang; Yan, Ming; Lin, Wei‐Yu; Chen, Kevin Sean; Ro, Tracy; Lipshutz, Gerald S.; Wu, Lily; Shi, Linqi; et al.
Abstract: Simultaneous delivery of multiple genes and proteins (e.g., transcription factors; TFs) is an emerging issue surrounding therapeutic research due to their ability to regulate cellular circuitry. Current gene and protein delivery strategies, however, are based on slow batch synthesis, which is ineffective, poorly controlled, and incapable of simultaneous delivery of both genes and proteins with synergistic functions. Consequently, advances in this field have been limited to in vitro studies. Here, by integrating microfluidic technologies with a supramolecular synthetic strategy, we present a high‐throughput approach for formulating and screening multifunctional supramolecular nanoparticles (MFSNPs) self‐assembled from a collection of functional modules to achieve simultaneous delivery of one gene and TF with unprecedented efficiency both in vitro and in vivo. We envision that this new approach could open a new avenue for immunotherapy, stem cell reprogramming, and other therapeutic applications. Abstract : Special delivery : Integration of microfluidic systems with a supramolecular synthetic strategy results in a high‐throughput approach to formulating and screening multifunctional supramolecular nanoparticles (see picture). The nanoparticles are self‐assembled from a collection of functional modules (proteins, genes, ligands, and a scaffold) and can simultaneously deliver both a gene and transcription factor either in vitro or in vivo.